1973
DOI: 10.1099/00222615-6-1-21
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Interferon and Virus Virulence in Influenza Virus Infections of the Mouse

Abstract: THERE have been many attempts to explain the virulence of viruses on the basis of their sensitivity to interferon or their ability to induce interferon in infected cells. Enders (1962) and De Maeyer and Enders (1965) observed that an attenuated strain of measles virus induced larger amounts of interferon than did a virulent strain, but considered that the poorer growth of the attenuated strain was probably not due to the increased production of interferon. Ruiz-Gomez and Isaacs (1963a) studied a number of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…:~ Probability P as indicated in Table I. (17). The susceptibility of immature Mx bearers may be related to their inability to make adequate amounts of interferon, rather than to their inability to respond to it.…”
Section: Resultsmentioning
confidence: 99%
“…:~ Probability P as indicated in Table I. (17). The susceptibility of immature Mx bearers may be related to their inability to make adequate amounts of interferon, rather than to their inability to respond to it.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these data indicate that the serum and lung inhibitors stimulated by 9-MS were interferon. DISCUSSION Influenza virus has generally been regarded as more sensitive to the action of interferon (17,20) than herpes simplex and other viruses (3). It has generally been reported that the prophylactic administration of such interferon inducers as polyinosinic:polycytidylic acid (injected i.p.…”
Section: Resultsmentioning
confidence: 99%
“…Influenza infection causes rapid induction of type I IFN secretion in the respiratory tract (2,3). IFN is a well-known family of antiviral cytokines that can be secreted by virtually all host cells (11).…”
mentioning
confidence: 99%